The Existence of the Nanas Madu Dance at the Tilamsari Art Studio in Pemalang Regency - Elwy Nur Sulistiana; Utami Arsih (Universitas Muhammadiyah Enrekang, 2025)
Traditional dance faces sustainability challenges amid globalization and the dominance of digital culture, including the Nanas Madu Dance, which represents the local culture of Pemalang Regency. This study aims to analyze the existence of the Nanas Madu Dance at Sanggar Seni Tilamsari and the preservation strategies applied. The research uses a descriptive qualitative method with a sociological approach to art and SWOT analysis. The findings show that Sanggar Tilamsari plays an active role in sustaining the dance through training, performances, and the use of digital media. However, challenges such as limited dancer regeneration, lack of promotional resources, and the influence of popular culture remain obstacles. Observations reveal that dance sustainability depends not only on aesthetic value but also on community participation and technological adaptation. This study recommends the need for policy support, digital literacy for art practitioners, and collaboration with educational institutions to strengthen local cultural preservation. These findings affirm that traditional arts remain relevant when they can evolve contextually. The Nanas Madu Dance is not merely a relic of the past, but a cultural opportunity for the future that must continue to be revitalized.